Measurement of Beauty in Architecture - Sahar Naieeb Kharrufa (Iraqi Journal of Architecture and Planning, 2009)
Several years ago an attempt was made to measure the beauty of thearchitectural design. The objective was to prepare the design for evaluation by acomputer. It was found that such measurement was very complicated and requiresmuch more research. Several more attempts were made to fill in ih" gup. but the totalpicture remained unclear. This paper attempts to draw a map for futuri work.The object of beauty in architecture depends on content and form. Contentincludes function and symbol. But the subject is complicated by the fact that beauty issubjective and changes according to viewer, time, and place.